From Confusion to Confidence: A Narrative Inquiry into ESP Students’ Learning through Google Sites E-Portfolios - Ammade, Salasiah; Nurhasanah; Herman, Shakira (Eduvelop: Journal of English Education and Development, 2025)
E-Portfolio has been widely used for academic preference for higher education. Yet, limited study on ESP students using E-portfolio still occur as well as study on English learning confidence for ESP. This study aims to explore the narrative confidence story of four students majoring in Nutrition Science at Universitas Muhammadiyah Parepare in using e-portfolios with the assistance of Google Sites in learning English. Using a narrative approach, the study focused on how this learning process affected their confidence in learning English. Data was collected through questionnaire responses from the four participants, who revealed their experiences from the initial confusion when learning English in the English for Specific Purpose (ESP) class to finally feeling proud and satisfied because of their improved English skills and successfully completing an English E-Book project as a final project. Thus, it continued to interview the participants to get in depth data. In analyzing data, the narrative analysis of Riessman (2008) and Barkhuizen (2013) was applied. The results showed that although they initially faced language challenges such as lack of vocabulary, low self-esteem in presenting English, lack of ability to write simple sentences as well as technical difficulties and lack of familiarity with the google sites platform for creating E-portfolio assignments, they gradually developed skills and confidence. E-portfolios helped them organize their assignments, improve their English language skills (especially speaking and writing), and enrich their knowledge in nutrition and culture. These findings highlight the potential of e-portfolios as a pedagogical tool that not only supports the learning of material, but also empowers students to feel more competent and confident in their learning process.